Dashboard para el análisis sobre la efectividad de los cultivos y su relación con el clima a partir de datos abiertos en Colombia (2022)
The dashboard is a technological methodology widely used in the world since it allows you to see how it is, how it was and how it would be if data were well processed, stored and managed in the information analysis process.